2023
DOI: 10.3389/fpsyg.2022.957235
|View full text |Cite
|
Sign up to set email alerts
|

Perceived meaning of life and satisfaction with life: A research synthesis using an online finding archive

Abstract: Introduction“Meaning” and “happiness” are leading topics in positive psychology, but their relationship is not well understood. The first step to better understanding is to inspect the pattern of correlations found in the research literature. Specifically, we seek answers to the following questions of fact: (1) Is there a correlation between perceived meaning of life and satisfaction with life? (2) If so, is that correlation positive or negative? (3) How strong is this correlation? (4) How variable is this cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The meaning-making theory suggests that as humans, we possess an innate need to derive meaning from our experiences and existence, as it can provide us with a sense of purpose, motivation, and fulfillment [4]. The study has indicated that a sense of meaning and purpose in life are positively associated with well-being, including life satisfaction [5], life support [6], and resilience [7], as well as negatively related to existential vacuum [8], depression, and anxiety [9]. Studying the role of ML after traumatic events, like the recent earthquakes in Turkey and Syria in 2023, can offer insights into the psychological processes that promote resilience and recovery among university students by focusing on the role of social support and ML.…”
Section: Introductionmentioning
confidence: 99%
“…The meaning-making theory suggests that as humans, we possess an innate need to derive meaning from our experiences and existence, as it can provide us with a sense of purpose, motivation, and fulfillment [4]. The study has indicated that a sense of meaning and purpose in life are positively associated with well-being, including life satisfaction [5], life support [6], and resilience [7], as well as negatively related to existential vacuum [8], depression, and anxiety [9]. Studying the role of ML after traumatic events, like the recent earthquakes in Turkey and Syria in 2023, can offer insights into the psychological processes that promote resilience and recovery among university students by focusing on the role of social support and ML.…”
Section: Introductionmentioning
confidence: 99%
“…Research has also emphasized that adjustment is an important factor influencing students’ subjective well-being ( 36 ). It has been noted that adolescents’ level of school adjustment positively predicts life satisfaction ( 37 ), and that both well-being and life satisfaction are related to meaning in life ( 38 ). Therefore internet adaptability may be predictive of life meaning.…”
Section: Introductionmentioning
confidence: 99%